Effect of digital mindfulness on perceived stress and anxious emotion among college students - Xiong, Weirui; Yu, Xia; Yu, Lu; Yang, Fan (Frontiers in Psychiatry, 2025)
BackgroundPerceived stress and anxiety are common psychological issues among college students. Traditional mindfulness interventions effectively ameliorate these psychological issues, while digital mindfulness interventions—an emerging approach—are gaining increasing attention owing to their convenience and accessibility.PurposeThis study aimed to assess the effectiveness of digital mindfulness in reducing perceived stress and anxiety among college students and to explore its potential effects on mindfulness.MethodsThe study employed a randomized controlled trial design and recruited 310 university students aged 18–22 years, randomly assigned to the intervention (N=156) or control (N=154) groups. The intervention group completed 4 weeks of mindfulness practice, engaging in 15–20 min guided sessions via social media 2–3 times per week. The control group did not receive any mindfulness training. The Chinese Perceived Stress Scale, Generalized Anxiety Disorder-7 scale, and Five Facet Mindfulness Questionnaire were used to assess participants’ stress perceptions, anxiety, and mindfulness levels at baseline and the end of the intervention.ResultsAt the end of the intervention, the intervention group reported significantly lower levels of perceived stress and anxiety and considerably higher levels of mindfulness. In contrast, the control group showed no significant changes in perceived stress, anxiety, or mindfulness levels.ConclusionsThe 4-week digital mindfulness intervention effectively reduced perceived stress and anxiety levels and increased mindfulness among college students.